APLIKASI DIAGNOSIS PENYAKIT PADA TUMBUHAN TOMAT BERBASIS WEBSITE - Niawati, Mirna; Ardhy, Ferly; Andika, Tahta Herdian; Bintoro, Panji (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Tomato fruit as a seasonal crop that is very popular in Indonesia, often faces obstacles in its production due to disease attacks that are often not identified by farmers, which ultimately has an impact on decreasing crop yields for farmers. In this study, researchers apply the if-then function in which it determines the type of disease based on data and facts from an expert. This research resulted in an application of diagnosing tomato plant diseases using the method of developing an extreme proggraming system, with the aim that this application can help farmers to diagnose the early stages of the type of disease based on the symptoms experienced.